Integrating Social and Field Data to Understand Farmers' Adoption of Biofertilizer in Rose Cultivation - Reginawanti Hindersah; Pujawati Suryatmana; Endah Yulia; Yeni Wispa Dewi; Aliya Zahrah Adawiah; Rara Rahmatika Risanti (Fakultas Pertanian, Universitas Pattimura Ambon, Indonesia, 2025)
The growing demand for sustainable agriculture has sparked interest in biofertilizers as an alternative to chemical fertilizers. However, adoption among farmers remains low, particularly in floriculture, due to limited knowledge and concerns about effectiveness. This study integrates social and field data to understand farmer perceptions and evaluate the impact of biofertilizers on the growth of Rose (Rosa hybrida L.) cv Hermosa. Primary data was collected through a focus group discussion (FGD) distributed to local farmers in Cikahuripan Village, Parongpong District. A field experiment was conducted using a Completely Randomized Block Design with three biofertilizer treatments: Control, Nitrogen-fixing Bacteria (NFB) - Phosphate-solubilizing microbes (PSM) consortium, and Bacillus Consortium. The FGD revealed that most farmers had never received biofertilizer knowledge and its application method, highlighting the need for better training and outreach. Experimental results showed that while plant height remained unaffected by biofertilizers in the early stages, the NFB-PSB consortium significantly boosted growth in later weeks. Both biofertilizers enhanced microbial populations, soil health, and flower diameter, proving their potential as eco-friendly alternatives to synthetic fertilizers. These findings emphasize the importance of bridging scientific innovation with farmer adoption to promote sustainable rose cultivation. Long-term studies and policy support are crucial for encouraging biofertilizer use in commercial floriculture.